2022
DOI: 10.1128/jvi.00765-22
|View full text |Cite
|
Sign up to set email alerts
|

The Host Response to Influenza A Virus Interferes with SARS-CoV-2 Replication during Coinfection

Abstract: The human population now has two circulating respiratory RNA viruses with high pandemic potential, namely, SARS-CoV-2 and influenza A virus. As both viruses infect the airways and can result in significant morbidity and mortality, it is imperative that we also understand the consequences of getting coinfected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 45 publications
6
35
0
Order By: Relevance
“…Comparably, similar SARS2 vRNA loads within respiratory tissues between 6--8-weeks old GSHs infected with SARS2 and co-infected with FLUAV (PR8) H1N1 were observed at 4 dpc [8]. While we observed a reduction of vRNA in the NT at 6 dpc, a recent report showed that prior FLUAV infection 14 days before SARS2 infection resulted in reduced SARS2 replication in the lung of male 6-8 weeks old GSH [36]. High SARS2 viral loads in respiratory samples, including NT, trachea, and lungs, at early time points, were also observed…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Comparably, similar SARS2 vRNA loads within respiratory tissues between 6--8-weeks old GSHs infected with SARS2 and co-infected with FLUAV (PR8) H1N1 were observed at 4 dpc [8]. While we observed a reduction of vRNA in the NT at 6 dpc, a recent report showed that prior FLUAV infection 14 days before SARS2 infection resulted in reduced SARS2 replication in the lung of male 6-8 weeks old GSH [36]. High SARS2 viral loads in respiratory samples, including NT, trachea, and lungs, at early time points, were also observed…”
Section: Discussionsupporting
confidence: 81%
“…These results suggest that previous innate immune response stimulation from FLUAV pre-exposure may influence the duration of opportunistic pathogen enrichment such as Haemophilus post-SARS2 infection. It has also been previously demonstrated that 6–8 week old GSH sustained heightened gene expression of interferon-stimulating genes 7 and 14 days post FLUAV infection [ 36 ]. The innate immune response, including macrophages and neutrophils, is important for viral clearance but also plays a role in regulating commensal microbes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research will have to show the relevance of our findings in the context of SARS-CoV-2/ influenza virus co-infection. Data on the severity of SARS-CoV-2/ influenza A virus co-infections are inconsistent in cell culture and animal models [Andrés et al, 2022; Kim EH et al, 2022; Kim HK et al, 2022; Oishi et al, 2022] and in humans [Cuadrado-Payán et al, 2020; Yue et al, 2020; Alosaimi et al, 2021; Stowe et al, 2021; Xiang et al, 2021; Krumbein et al, 2022; Swets et al, 2022]. This may not be a surprise, given the differences in interferon signalling between different SARS-CoV-2 variants that we present here and that were described in previous studies [Alfi et al, 2022; Bojkova et al, 2022; Bojkova et al, 2022a; Guo et al, 2022; Thorne et al, 2022].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has also been observed in mouse models of SARS-CoV, MERS-CoV, and IAV infection [17] . On the other hand, early IFN/ISG responses elicited by co-infection with rhinovirus or IAV can substantially block SARS-CoV-2 replication 13 , 18 , indicating that delaying IFN responses represents a major strategy of immune evasion by SARS-CoV-2.…”
Section: Ifn Dysregulation and Its Role In Covid-19 Pathogenesismentioning
confidence: 99%